2014
DOI: 10.1073/pnas.1319538111
|View full text |Cite
|
Sign up to set email alerts
|

The changing face of cognitive gender differences in Europe

Abstract: Cognitive gender differences and the reasons for their origins have fascinated researchers for decades. Using nationally representative data to investigate gender differences in cognitive performance in middle-aged and older populations across Europe, we show that the magnitude of these differences varies systematically across cognitive tasks, birth cohorts, and regions, but also that the living conditions and educational opportunities individuals are exposed to during their formative years are related to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
98
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 29 publications
(45 reference statements)
19
98
0
1
Order By: Relevance
“…In light of evidence showing that these differences vary substantially across nations, and mirror the gender inequalities in education, employment opportunities, and career achievements in particular countries, researchers have suggested that improved standards of living and educational opportunities in populations with lower economic development levels may improve the cognitive performance levels in these populations, especially among women (Baker and Jones 1993;Else-Quest et al 2010;Weber et al 2014). …”
Section: Sex Differences In Cognitive Functionmentioning
confidence: 99%
“…In light of evidence showing that these differences vary substantially across nations, and mirror the gender inequalities in education, employment opportunities, and career achievements in particular countries, researchers have suggested that improved standards of living and educational opportunities in populations with lower economic development levels may improve the cognitive performance levels in these populations, especially among women (Baker and Jones 1993;Else-Quest et al 2010;Weber et al 2014). …”
Section: Sex Differences In Cognitive Functionmentioning
confidence: 99%
“…For example, cognitive functioning is studied using one set of measures (Weber et al 2014;Skirbekk, Loichinger and Weber 2012;Schneeweis, Skirbekk and Winter-Ebmer 2014;Stoet and Geary 2013;Flynn 1987), and physical functioning is studied using another set of measures (Leong et al 2015;Sanderson and Scherbov 2014;Al Snih et al 2004;Habibi et al 2013;Innes 1999). It might be possible to determine that both cognitive and physical functioning improved over time in a particular country, but even in that case there would be no natural way to compare these changes.…”
Section: Introductionmentioning
confidence: 99%
“…A recent cross-country comparison of gender differences in cognition over time indicate that cognitive performance of the population increased in Northern Europe as these countries grew richer. Notably, women's cognitive performance has surged, causing the gender gap to narrow in tasks that men used to have a distinct advantage in (numerical skills), and widening the gap in skills where women have always had an advantage (verbal skills and short-term memory) (Weber et al, 2013). These trends were also evident in the relatively poorer countries of Southern Europe, but on a more modest scale.…”
Section: Introductionmentioning
confidence: 99%